Labconcept Group Solutions for Pharmaceutical Industry - article Editorial (Разработка и регистрация лекарственных средств)
The Labconcept Group is the official distributor of leading manufacturers of analytical and general laboratory equipment. Labconcept offers comprehensive solutions for equipping laboratories of various fields, including for the pharmaceutical industry. The pharmaceutical industry in Russia continues to develop and expand the volumes of manufactured medicines, which inevitably entails the need to create new and expand existing laboratories for quality control of manufactured drugs. Under the conditions of sanctions pressure, many familiar manufacturers of analytical equipment have left the market. At the same time, there is a growing need for reliable and efficient analytical and testing equipment. The Labconcept Group offers solutions that have been tested in own laboratory, in particular, dissolution testers from Haosoo Instruments (Hanon Group) and total organic carbon analyzers under its own OEM brand SILab. Both lines of devices comply with the requirements of the US Pharmacopoeia, the European Pharmacopoeia and the State Pharmacopoeia of the Russian Federation.